2010
DOI: 10.1128/mcb.01145-09
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Signaling, a Mechanism for Cellular Stress Resistance in Long-Lived Mice

Abstract: Transcriptional regulation of the antioxidant response element (ARE) by Nrf2 is important for the cellular adaptive response to toxic insults. New data show that primary skin-derived fibroblasts from the long-lived Snell dwarf mutant mouse, previously shown to be resistant to many toxic stresses, have elevated levels of Nrf2 and of multiple Nrf2-sensitive ARE genes. Dwarf-derived fibroblasts exhibit many of the traits associated with enhanced activity of Nrf2/ARE, including higher levels of glutathione and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 112 publications
(121 reference statements)
9
117
1
1
Order By: Relevance
“…These features are recapitulated by observations in human fibroblasts and by other studies showing that chronic activation of mTORC1 with IGF-1 reduces proliferative potential and causes accumulation of damaged mitochondria and ROS, leading to cellular senescence (Bitto et al 2010b;Handayaningsih et al 2012). Conversely, long-lived Snell/Dwarf mice show increased basal activation of the NFE2L2 pathway, suggesting that IIS and the antioxidant response cooperate to influence longevity (Leiser and Miller 2010). In fact, Snell/Dwarf mice-derived fibroblasts show lower levels of mTORC1 activity and enhanced autophagy in response to stress (Wang and Miller 2012).…”
Section: P62/sqstm1: a Novel Aging Genesupporting
confidence: 66%
See 1 more Smart Citation
“…These features are recapitulated by observations in human fibroblasts and by other studies showing that chronic activation of mTORC1 with IGF-1 reduces proliferative potential and causes accumulation of damaged mitochondria and ROS, leading to cellular senescence (Bitto et al 2010b;Handayaningsih et al 2012). Conversely, long-lived Snell/Dwarf mice show increased basal activation of the NFE2L2 pathway, suggesting that IIS and the antioxidant response cooperate to influence longevity (Leiser and Miller 2010). In fact, Snell/Dwarf mice-derived fibroblasts show lower levels of mTORC1 activity and enhanced autophagy in response to stress (Wang and Miller 2012).…”
Section: P62/sqstm1: a Novel Aging Genesupporting
confidence: 66%
“…Continuous, irreparable damage to DNA, proteins, and organelles can be caused by oxidants, radiations, and other insults through free radical reactions (Harman 2003), progressively impairing cellular homeostasis. Living organisms are well equipped with detoxifying, antioxidant, and repair enzymes to cope with this kind of damage (RobidaStubbs et al 2012;Longo 1999;Steinbaugh et al 2012;Leiser and Miller 2010;Salmon et al 2005;Wei et al 2008): this suggests that raising the cellular defenses against stressors would mimic the effects of ageextending interventions. In addition to stress resistance, cellular homeostasis is also influenced by quality control mechanisms that regulate function, structure, and degradation of cellular components, such as the proteinfolding machinery, mitochondrial fission and fusion dynamics, the ubiquitin-proteasome system, and autophagy (Koga et al 2011;Seo et al 2010).…”
mentioning
confidence: 99%
“…Although we cannot rule out effects at other targets by the individual constituents of the mixture of compounds contained in Prot, the increase in expression of xenobiotic response genes in the livers of mice in the present study at the 1200 ppm dose (data not shown) further supports the idea that the effects of Prot on longevity may be at least partly due to Nrf2 activation. For example, Leiser & Miller (2010) reported that primary skin‐derived fibroblasts from the long‐lived Snell dwarf mutant mouse manifest elevated levels of Nrf2, higher levels of glutathione, and increased resistance to plasma membrane lipid peroxidation. Consistent with those findings, mRNA levels for Nrf2‐sensitive genes were reported to be elevated in selected tissues of Snell dwarf mice (Leiser & Miller, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…References; 1, Brown-Borg et al 2001;2, Brooks et al 2007;3, Hauck et al 2002 IIS insulin/IGF-1 signalling pathway mutant Irs1 −/− ; insulin receptor substrate-1 knockout GH growth hormone GHRKO growth hormone receptor/binding protein knockout M male and F female a Significant difference at young (3 months) but no difference at old age (24 months) b Significant difference at old age (24 month) but no difference at young age (3 months) c MDA+4-HNE; significant differences at middle-age (12 months) and old age (24 months) but no differences at young age (3 months) levels have previously been shown to be increased in brain, liver, and muscle tissue of Ames dwarf mice (Brown-Borg and Rakoczy 2003), as well as in dermal fibroblasts of Snell dwarf mice (Leiser and Miller 2010). Perhaps surprisingly, we observed no difference in protein (carbonyls) or lipid (4-HNE) oxidative damage in brain, skeletal muscle, or liver between Irs1 −/− and WT mice.…”
Section: Nsmentioning
confidence: 99%